Economic Growth and Islamic Financial Inclusion in OIC Countries: Evidence with Spline Approach - Idris, Aditya (International Journal of Islamic Finance, 2025)
Background: Digital financial inclusion is presently one of the most acknowledged domains of international development. Financial inclusion is pertains to the accessibility of inexpensive financial services for individuals and enterprises to fulfill their requirements.   Objectives: This study aims to analyze the effect of Islamic financial inclusion on economic growth in Organisation of Islamic Cooperation (OIC) member countries, focusing on the importance of financial infrastructure and digital adoption in Muslim-majority nations. Novelty: This study presents a novel methodology by analyzing the correlation between economic growth and Islamic financial inclusion in the context of OIC (Organization of Islamic Cooperation) nations with a Spline regression model. This research explicitly examines Islamic financial inclusion, a neglected aspect that adheres to the norms and practices of Sharia law, in contrast to traditional studies that address financial inclusion in a general sense. Research Methodology / Design: The research employs the Spline regression approach to capture the non-linear relationship between Islamic financial inclusion and economic growth. The dependent variable is economic growth represented by GDP per capita, while the independent variables consist of the number of ATMs, Islamic bank branches, mobile phone usage, and internet access. The study uses data from 47 OIC member countries, with independent variables from 2022 and the dependent variable from 2023. Findings: The results indicate that the maturity level of financial infrastructure and the adoption of technology significantly contribute to economic growth. The separation of indicators based on their influence provides valuable insights for policymakers to design more targeted financial inclusion strategies. Furthermore, the findings highlight that access to financial services, digital adoption, and Islamic financial practices play a transformative role in improving GDP per capita across OIC countries. Implication: The findings provide both theoretical and practical implications by demonstrating that tailored financial inclusion policies are needed to accommodate diverse national contexts and stages of economic development in OIC member states.